Auto-organização de partículas patchy carregadas - Araujo, Jorge Luiz Bezerra de (2014)
The current stage of development of experimental techniques allow the synthesis of particles complex colloidal, whose surface can be precisely "decorated" with physical properties and/or chemical combinations. Such colloids are usually defined as patchy particles. As result of the modification of parts of the surface of such particles, the interaction between them is generally characterized by an anisotropic potential. Study and understand the process of self-organization of this particular system is of great interest both from the scientific point of view as technology, because of its use in functional materials. In this dissertation, we study. The behavior of a two-dimensional system patchy charged particles, in which the surface is decorated with a timely charge sign opposite that located in the particle center. Thus, patchy each particle has a net charge C, which is result of the difference between the point charges on the surface and that in the particle center patchy. This study uses the technique of computer simulation of molecular dynamics to study the process of self-organization of particles patchy depending on the density and temperature. Initially, we present the model of patchy particles studied here and there is the behavior of the interaction energy between two particles and its dependence on load effective particle (liquid charge) and the number of active sites (p) that decorate the surfaces of colloids, called patches . The study of these parameters is important for understanding the self-organized structures obtained. Presents the stable structures of minimum energy a system with p=2 and C=0 as a function of temperature and density. In general, we observe two well defined phases were distinguished by calculation of thermodynamic properties during the simulation. Results for different values of p and C are also presented order to show the influence of this parameter in the system configuration. In general, it is observed that for large values of the charge and/or number of patches, the repulsive potential prevails causing the system to stabilize in a crystalline configuration. On the other hand, for a system composed of particles with a low value of charge and/or the number od patches interaction potential is attractive inducing predominantly resulting composite structures in the form of clusters of ring and lines particles.